SALURAN KOMUNIKASI PENYULUHAN DALAM MENINGKATKAN PENGETAHUAN PETANI KOPI DI DESA ATAKU KECAMATAN ANDOOLO KABUPATEN KONAWE SELATAN - Sunan Aji Wibowo; Ima Astuty Wunawarsih; Megafirmawanti Lasinta; Rahayu Endah Purwanti (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Agricultural extension plays a strategic role in empowering coffee farmers in Ataku Village, South Konawe Regency, through effective communication to improve their knowledge, skills, and productivity in coffee farming, which is still low despite its great potential. This study aims to determine the channels of agricultural extension communication in improving the knowledge of coffee farmers in Ataku Village, Andoolo District, South Konawe Regency. This study uses a quantitative approach with a descriptive survey method that aims to systematically describe the extension communication channels and the level of knowledge of coffee farmers. The research population consists of all 150 coffee farmers in Ataku Village. The research sample was determined using simple random sampling, with the research sample set at 20% of the total population, or 30 people. The research variables included extension communication channels and coffee farmers' knowledge. The data were analyzed using quantitative descriptive analysis. The results showed that agricultural extension communication channels played an important role in increasing the knowledge of coffee farmers in Ataku Village, Andoolo District, South Konawe Regency. Mass communication through a group approach was the most dominant channel, with print media (especially extension brochures) being the most effective medium because it was easy to understand and could be used as a continuous reference. Audiovisual media served as a complement that helped visualize technical information and encourage discussion, although its use was still relatively limited. The impact of using these communication channels is reflected in the change in farmers' knowledge, which is in the moderate category, with a high level of understanding, but the ability to apply and integrate knowledge in farming practices is still not optimal. The effectiveness of extension communication needs to be strengthened through media synergy and continuous assistance so that increased knowledge can encourage the application of coffee farming innovations more effectively and sustainably.